Optimizing Research to Speed Up Availability of Pediatric Antiretroviral Drugs and Formulations. (10th March 2017) - Penazzato, Martina; Gnanashanmugam, Devasena; Rojo, Pablo; Lallemant, Marc; Lewis, Linda L; Rocchi, Francesca; Saint Raymond, Agnes; Ford, Nathan; Hazra, Rohan; Giaquinto, Carlo; Belew, Yodit; Gibb, Diana M; et al.
Abstract : Only 51% of eligible HIV-infected children actually start treatment, and research and development (R&D) for pediatric antiretrovirals lags considerably behind that of adults. We highlight innovative approaches to R&D that will enable simplified and faster strategies to develop optimal formulations. Abstract: Globally 1.8 million children are living with human immunodeficiency virus (HIV), yet only 51% of those eligible actually start treatment. Research and development (R&D) for pediatric antiretrovirals (ARVs) is a lengthy process and lags considerably behind drug development in adults. Providing safe, effective, and well-tolerated drugs for children remains critical to ensuring scale-up globally. We review current approaches to R&D for pediatric ARVs and suggest innovations to enable simplified, faster, and more comprehensive strategies to develop optimal formulations. Several approaches could be adopted, including focusing on a limited number of prioritized formulations and strengthening existing partnerships to ensure that pediatric investigation plans are developed early in the drug development process. Simplified and more efficient mechanisms to undertake R&D need to be put in place, and financing mechanisms must be made more sustainable. Lessons learned from HIV should be shared to support progress in developing pediatric formulations for other diseases, including tuberculosis and viral hepatitis.